Serum Cytokeratin-18 as a Non-invasive Biomarker and its Association with Biochemical Parameters in the Diagnosis of Non-alcoholic Fatty Liver Disease - Albeltaji, Ali; Al-qatati, Abeer; Alzaharna, Mazen (Jordan Medical Journal, 2024)
Objective: Nonalcoholic fatty liver disease (NAFLD) is one of the chronic silent diseases in which its therapeutic options and noninvasive markers of disease activity and severity remain limited. We aimed in this study to assess cytokeratin-18 (CK18) as a new non-invasive biomarker to distinguish between NAFLD stages and its correlation with some biochemical parameters. Methods: A case control study was conducted on a sample of 90 subjects aged 12-79 years, categorized into three groups (nonalcoholic steatohepatitis "NASH", steatosis and controls). CK18, fasting blood glucose (FBG), lipid profile parameters, aspartate aminotransferase (AST), alanine aminotransferase (ALT), urea, and creatinine were determined. Low destiny lipoprotein-cholesterol (LDL-C), and body mass index (BMI) were calculated in addition to performing complete blood count (CBC). Results: The results indicate that the mean level of serum CK18 in NASH cases was significantly higher than steatosis and control groups. CK18 has a positive correlation with triglycerides (TG) total cholesterol (TC), ALT, AST, FBG, urea, creatinine, age, BMI, and LDL-C, and a negative correlation with high density lipoprotein-cholesterol HDL-C. Finally, ROC curve showed that the sensitivity of CK18 test is 77.1% and specificity is 96.6%. The cut-off value for CK18 test is 161 U/L. Conclusions: In this study, a significant relationship was observed between CK18, hepatic enzymes, and NAFLD degrees. CK18 has good accuracy, sensitivity, and specificity in diagnosing NASH.